Elisha's profile in the Book of Kings: the double agent - Bodner, Keith (Oxford University Press, 2013)
'Elisha's Profile in the Book of Kings' uses the tools of literary criticism to read the Elisha narrative as an integral component of the Deuteronomistic History compiled in the aftermath of the Babylonian invasion and destruction of Jerusalem in 586 BCE.